Efek Pembelajaran Online terhadap High Order Thinking Skills pada Siswa Biologi pada Masa Pandemic Covid-19 - Amin, Astuti Muh; Karmila, Fitriyah; Muna, Lintal; Hujjatusnaini, Noor; Adiansyah, Romi; Yani, Ahmad (Jurusan Pendidikan Biologi - Universitas Siliwangi, 2022)
Along with the development of the 21st century, students are required to have high order thinking skills (HOTs). Online teaching and learning has become a necessity for education around the world during the COVID-19 pandemic. The sudden change in the learning process during the Covid-19 pandemic had a very significant impact on various aspects of learning, including HOTs. The purpose of this study was to determine the effect of online learning on high order thinking skills in biology students in the city of Ternate. This research is a quantitative descriptive research. Describe the effect of online learning on high order thinking skills. The population in this study were biology students at a public high school in the city of Ternate, North Maluku, Indonesia. The sampling technique was done by purposive sampling. The research sample was biology students at SMA Negeri 4 Ternate and SMA Negeri 8 Ternate, North Maluku with a total of 56 students. The research was conducted in the odd semester of the 2021/2022 academic year. The instrument used in this research is an instrument to measure high order thinking skills. The results of this study indicate that the average total high order thinking skills of biology students for analyzing level is 50.44; level evaluate 45.38; levels creating 41.16. This indicates that more efforts are still needed so that students can have adequate HOTs abilities.